Argumen Pendidikan Seksual Dalam Al-Qur’an (Upaya Penanggulangan Transeksual Pada Anak) - Siti Khoeriyah; Ahmad Zain Sarnoto; Hamdani Anwar (Journal on Education, 2024)
This research aims to Argumens of the Qur'an in the context of sexual education as a solution to prevent the phenomenon of transsexuality in children. The conclusion of this research asserts that Quranic-based sexual education Argumens are not only preventive measures but also effective instruments in combating the negative impacts on children's development and have high relevance in providing protection against the adverse effects of transsexuality on children, exploring efforts to counter transsexuality in children through Quranic-based sexual education. The research conclusion is obtained through critical analysis of the phenomenon of transsexuality from the historical perspectives of religion, psychology, and law. This research is then followed up with a thematic interpretation approach based on Quranic references concerning Argumens of sexual education and transsexuality in children. The methods used in this research are qualitative research with the maudhȗ’î interpretation method and historical-critical-contextual methods. Meanwhile, the approach used is a qualitative method based on literature research, Quranic verses, research publication, journals, conference or seminar proceedings, interviews, and articles